The exotic jumping snail ovachlamys fulgens (Gude, 1900) (gastropoda: Helicarionidae) in urban areas of the Upper-Paraná Atlantic forest - Beltramino, Ariel Anibal (2018)
The exotic land gastropod Ovachlamys fulgens (Gude, 1900), aka the jumping snail, was registered in Eldorado city, Misiones province, constituting the first documented record of that species in Argentina- and for all of South America as well. Identities of the individuals were confirmed through morphological examination, and by a DNA sequencing of the cytochrome oxidase subunit I gene. DNA sequences for the mitochondrial 16S-rRNA and the nuclear 18S-rRNA genes were also obtained from the morphologicallyconfirmed specimens to gain insights into the genetic background of this species in Argentina, and as additional markers for enhancing the rapidity of identification by governmental authorities who are responsible for managing the presence of exotic species. Different size classes suggested that the species had successfully reproduced and become established in the locality. Ovachlamys fulgens is emphasized in the literature as being a serious pest to orchids. Misiones province harbors a high species richness of orchids, representing about one half of the known species in Argentina. Owing to the use of the orchid as an ornamental plant, the commercial trade could have facilitated the introduction of the species into Argentina. Control measures, preventive education, and surveillance are needed to prevent the further spread of this snail.